ChatGPT Utilization Strategy in Story-Based Marketing: Enhancing Consumer Engagement through Interactive Narratives - Sukistanto (PT. LITERASI SAINS NUSANTARA, 2024)
Story-based marketing has become an increasingly popular approach in modern marketing strategies. AI technology, such as ChatGPT, has enabled more personalized interaction between brands and consumers. This research aims to examine the strategy of using ChatGPT in story-based marketing to enhance consumer engagement through interactive narratives. The research method employed is a literature review with a qualitative approach and descriptive analysis. Descriptive analysis will be utilized to present and interpret data from 28 articles selected from Google Scholar between 2008-2023. The study's findings indicate that the use of interactive narratives supported by technology like ChatGPT offers significant opportunities for marketers to deepen consumer engagement and create more personalized experiences in marketing. Through dynamic and adaptive interaction, ChatGPT enables marketers to craft compelling and individually relevant stories, as well as opens doors for collaboration between brands and consumers. However, challenges such as the risk of losing control over brand messages and the need for ethical compliance and privacy regulation must be carefully addressed.